PUBLIC ADMINISTRATION OF DIGITAL SMART INFRASTRUCTURE IN UKRAINE: UNDER THE CONDITIONS OF THE MARITAL STATE REGIME AND IN THE POST-WAR PERIOD - STRELCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Considering Russia’s war in Ukraine, it is rather difficult to apply the current trends in the development of modern cities in Ukraine to the trends in the development of modern cities in Ukraine. The current trends in the development of modern cities in Ukraine are quite difficult to fit into the pan-European scenario of smart urban development. It is rather difficult to fit into the pan-European scenario of smart urban development. Even before the war, various institutional problems arose, such as political and economic instability, aggravation of geopolitical problems. A number of institutional problems, including the growth of geopolitical risks, significantly inhibited the gradual movement of urban development in Ukraine. Large cities of Ukraine hindered progressive steps aimed at improving municipal services, strengthening intercity cooperation, and urban development. Large cities of Ukraine are improving municipal services and deepening mutual integration in order to increase the comfort of citizens. This is done in order to increase the comfort of citizens. That is why the primary task of the development of SMART-infrastructure in the conditions of today and in the post-war period is the characterization and research of key categories that reveal the essence and meaning of "smart city" as an object of public administration, which is an object of administration in the system of providing for its citizens an improved set of services. The presented article is directed directly to such problems.